2006
DOI: 10.1074/jbc.m513617200
|View full text |Cite
|
Sign up to set email alerts
|

HCELL Is the Major E- and L-selectin Ligand Expressed on LS174T Colon Carcinoma Cells

Abstract: When confined to a primary site (early stage disease), the five-year survival rate from colon cancer is ϳ90%. However, when disseminated from primary sites (metastatic), survival drops precipitously to 8%. These dramatic survival statistics underscore the need to define the pathobiology of the metastatic process to devise novel interventions to prevent or inhibit colon cancer spread. Hematogenous metastasis occurs as a highly regulated cascade of events, initiated by the escape of tumor cells from the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 34 publications
4
87
3
Order By: Relevance
“…Fluorography of samples from total cell extract, flowthrough and fucose-eluted fractions is shown in Figure 6b. Again, no 35 S-labeled proteins could be seen in eluted fractions (Elu) from parental cells, while three major proteins of 50, 80 and 150 kDa were retained on UEA-1 column from FUT1-expressing cell extract. These data are in accordance with those from MAL staining and GC-MS analysis (see Fig.…”
Section: E-selectin Ligand Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorography of samples from total cell extract, flowthrough and fucose-eluted fractions is shown in Figure 6b. Again, no 35 S-labeled proteins could be seen in eluted fractions (Elu) from parental cells, while three major proteins of 50, 80 and 150 kDa were retained on UEA-1 column from FUT1-expressing cell extract. These data are in accordance with those from MAL staining and GC-MS analysis (see Fig.…”
Section: E-selectin Ligand Characterizationmentioning
confidence: 99%
“…35 HepG2 cells, which also interact with both E-and L-selectin and express two major sLe x -protein carriers of 80-90 and 150 kDa (this study), has been reported to express the CD44 proteins. 36 It is therefore tempting to investigate whether our two KM93-positive proteins are related to the CD44.…”
Section: E-selectin Ligand Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated PBMC were Ͼ90% T cells (CD3ϩ cells) and expressed L-selectin as determined by immunofluorescent staining and flow cytometry using a Beckman-Coulter model Cytomics FC 500 MPL (Fullerton, CA Shear-dependent Binding Assays-Cell-cell interactions were studied by growing cells in standard tissue culture-treated 6-well plates. A circular parallel plate flow chamber apparatus (GlycoTech, Gaithersburg, MD) with internal flow chamber dimensions of 2 ϫ 0.5 ϫ 0.025 cm was mounted over the unfixed live cell monolayer (HNSCC cells) or fixed cell monolayer (KG1a and LS174T cells) within a well and sealed using low wall suction as described previously (18,19). The system was then equilibrated with Hanks' balanced salt solution (Invitrogen) supplemented with 10 mM HEPES, pH 7.4, and 2 mM CaCl 2 (binding buffer).…”
Section: Methodsmentioning
confidence: 99%
“…Cancer cells characteristically express CD44, and there is increasing evidence that HCELL serves as their major selectin ligand. This finding clarifies the ability of solid tumors to infiltrate bone marrow that is both HCELL and CXCR4 dependent [137][138][139] . Variations in CD44 are reported as cell surface markers for breast cancer stem cells.…”
Section: Cd44mentioning
confidence: 77%